Use of hormone therapy in gynaecological oncology and therapy of breast cancer - Lindert, Olaf; Skrzypulec-Plinta, Violetta; Plinta, Ryszard; Chełmicki, Zbigniew; Śmiszek-Lindert, Wioleta (Menopause Review/Przegląd Menopauzalny, 2010)
This article presents a review of new literature regarding hormonal therapy of female reproductive system tumours. Hormonal treatment in gynaecological oncology has to retard the course of neoplastic disease and decrease the intensity of its symptoms in patients with hormonally dependent breast cancer, endometrial cancer or ovarian cancer. Drugs belonging to different pharmacological groups are used in hormonal therapy in oncological gynaecology. Hormone therapy is established as an important method of therapy or support for oncological treatment. The physician dealing with therapy of neoplastic diseases has to remember about the advantages and risks of such treatment, and every case should be considered individually.